EXPERIMENTAL INVESTIGATION ON WORKABILITY, MECHANICAL PROPERTIES & THERMAL EFFECT OF POLYMER FIBER REINFORCED CONCRETE (STYRENE BUTADIENE RUBBER (SBR), POLYPROPYLENE ROPE) USING BRICK AND NATURAL AGGREGATE - Muhammad Sohaib Khan; Engr. Dr. Zaheer Ahmed; Engr. Dr. Naveed Anjum; Hassan Nisar; Muhammad Zeeshan; Muhammad Azhar; Kamran Hassan; Ikhtesham Ul Haq; Arif Hussain (Spectrum of Engineering Sciences, 2025)
This study investigates the workability, mechanical properties, and thermal effects of polymer fiber-reinforced M20-grade concrete with varying aggregate compositions The experimental program evaluates four concrete mixes: (1) Control mix with 100% natural aggregate (without polymer and fiber), (2) 100% natural aggregate (with polymer and fiber), (3) 50% natural + 50% brick aggregate with polymer and fiber, (4) 100% brick aggregate with polymer and fiber, and assessment of thermal conductivity effect for each mix. A fixed 10% polymer ratio was maintained, while the polypropylene rope fiber content varied from 0% to 1%. The fresh concrete was evaluated for workability using the slump test, while hardened properties were assessed through compressive strength, split tensile strength, and flexural strength tests at 7 and 28 days also analyzing thermal conductivity and insulation performance. Results indicated that increasing fiber content reduced workability but improved mechanical properties up to an optimum fiber dosage. Incorporating brick aggregates enhanced thermal insulation properties but led to a minor reduction in mechanical strength. This study highlights the feasibility of polymer fiber-reinforced concrete with hybrid aggregates for sustainable and durable construction applications.